Intraspecific Variation of Eysarcoris guttigerus (Hemiptera: Pentatomidae) in Japanese Southwest Population Based on Mitochondrial DNA. Issue 1 (21st January 2016) - Yamaji, Takuya; Ishikawa, Tadashi; Nomura, Masashi
Abstract: The white-spotted globular bug Eysarcoris guttigerus (Thunberg) (Hemiptera: Pentatomidae) is widely distributed in East Asia and the Pacific region. In Japan, the species is found in grassy or composite weeds in the western area of the main islands and Ryukyu Islands of Japan. One notable characteristic of the Eysarcoris genus is the two white spots on the scutellum. This is not the case with the Ishigaki Island population, however, which sports red spots instead of white, suggesting that intraspecific variation exists in the species. Therefore, we investigated intraspecific variation in E. guttigerus using mitochondrial NADH dehydrogenase subunit 2 ( ND2 ), cytochrome oxidase subunit 1 ( CO1 ), cytochrome b ( Cytb ), tRNA-Serine ( tRNA ser ), NADH dehydrogenase subunit 1 ( ND1 ), and 16S ribosomal RNA ( 16SrRNA ) genes from 13 populations of Japan. The obtained maximum likelihood phylogenetic tree was divided into three groups—Group 1: Mainland, Group 2: Central Ryukyu Islands (Okinawa-Amamioshima Islands), and Group 3: South Ryukyu Islands (Ishigaki Island). The Ishigaki population was significantly separated from the other populations with consistent differences in spot color. The estimated period of divergence between the Ishigaki population and the other populations was consistent with the period of formation of the Kerama Gap in the Ryukyu arc. Thus, the process of formation of the Kerama Gap may have influenced the intraspecific variation of E. guttigerus .